Memorizing And Understanding The Qur'an In Arabic Language Among Malaysian Students Of The Al-azhar Institute Of Qiraat Shobra, Egypt - Ashraf Ismail; Nurul Hudaa Hassan; Akhdiat Abd Malek; Abur Hamdi Usman (Humanities and Social Sciences Reviews, 2024)
Indexed by Scopus